Quantitative Apparent Diffusion Coefficient Derived From Diffusion-Weighted Imaging Has the Potential to Avoid Unnecessary MRI-Guided Biopsies of mpMRI-Detected PI-RADS 4 and 5 Lesions. Issue 12 (December 2018) - Polanec, Stephan H.; Helbich, Thomas H.; Bickel, Hubert; Wengert, Georg J.; Pinker, Katja; Spick, Claudio; Clauser, Paola; Susani, Martin; Shariat, Shahrokh; Baltzer, Pascal A.T.
Abstract : Objective: The aim of this study was to evaluate the potential of diffusion-weighted imaging–derived apparent diffusion coefficient (ADC) measurements to obviate unnecessary biopsies in multiparametric MRI–detected PI-RADS 4 and 5 lesions. Materials and Methods: This retrospective, institutional review board–approved study investigated 101 PI-RADS 4 and 5 prostate lesions (52 malignant, 49 benign) verified by in-bore MRI-guided biopsy in 101 men (mean age, 62.8 years). Two readers, who were not aware of the biopsy results independently and repeatedly measured minimum, mean, and maximum ADC from diffusion-weighted imaging measurements (in line with PI-RADS v2 recommendations) using a 2-dimensional region of interest drawn around the biopsied lesions. Diagnostic performance was evaluated using receiver operating characteristic statistics and reproducibility statistics were calculated. Results: The best diagnostic performance (overall area under the receiver operating characteristic curve [AUC] R1: 0.801; R2: 0.796 peripheral zone AUC R1:0.814, R2: 0.805; transitional zone AUC R1:0.786, R2:0.779) and the tightest limits of interreader agreement (−8.6% to 9.9%) were found in minimum ADC values. Rule-in and rule-out thresholds for diagnosis of prostate cancer were identified, demonstrating a potential to avoid unnecessary biopsies in 32.7% (16/49). Conclusions: Quantitative ADC measurement in multiparametric MRI–detected PI-RADS 4 and 5 lesions has the potential to avoid unnecessary MRI-guided biopsies in up to 33%.